Effects of intraoperative PEEP optimization on postoperative pulmonary complications and the inflammatory response: study protocol for a randomized controlled trial - Zoltán Ruszkai; Erika Kiss; Ildikó László; Fanni Gyura; Erika Surány; Péter Töhötöm Bartha; Gergely Péter Bokrétás; Edit Rácz; István Buzogány; Zoltán Bajory; Erzsébet Hajdú; Zsolt Molnár (Trials, 2017)
Abstract Background Patients undergoing general anesthesia and mechanical ventilation during major abdominal surgery commonly develop pulmonary atelectasis and/or hyperdistention of the lungs. Recent studies show benefits of lung-protective mechanical ventilation with the use of low tidal volumes, a moderate level of positive end-expiratory pressure (PEEP) and regular alveolar recruitment maneuvers during general anesthesia, even in patients with healthy lungs. The purpose of this clinical trial is to evaluate the effects of intraoperative lung-protective mechanical ventilation, using individualized PEEP values, on postoperative pulmonary complications and the inflammatory response. Methods/design A total number of 40 patients with bladder cancer undergoing open radical cystectomy and urinary diversion (ileal conduit or orthotopic bladder substitute) will be enrolled and randomized into a study (SG) and a control group (CG). Standard lung-protective ventilation with a PEEP of 6 cmH2O will be applied in the CG and an optimal PEEP value determined during a static pulmonary compliance (Cstat)-directed PEEP titration procedure will be used in the SG. Low tidal volumes (6 mL/Kg ideal bodyweight) and a fraction of inspired oxygen of 0.5 will be applied in both groups. After surgery both groups will receive standard postoperative management. Primary endpoints are postoperative pulmonary complications and serum procalcitonin kinetics during and after surgery until the third postoperative day. Secondary and tertiary endpoints will be: organ dysfunction as monitored by the Sequential Organ Failure Assessment Score, in-hospital stay, 28-day and in-hospital mortality. Discussion This trial will assess the possible benefits or disadvantages of an individualized lung-protective mechanical ventilation strategy during open radical cystectomy and urinary diversion regarding postoperative pulmonary complications and the inflammatory response. Trial registration ClinicalTrials.gov, ID: NCT02931409 . Registered on 5 October 2016.